Preparation of multicompartment sub-micron particles using a triple-needle electrohydrodynamic device. - Labbaf, S; Deb, S; Cama, G; Stride, E; Edirisinghe, M (2013)
Control over the size and morphology of polymeric carriers for drug delivery systems is essential to optimize their functionality. In the current study, we demonstrate the feasibility of using an electrohydrodynamic process with a triple-needle device to prepare nearly mono-dispersed, spherical, tri-layered sub-micron particles. Three biocompatible polymer solutions of poly (lactic-co-glycolic acid) (PLGA), polycaprolactone (PCL) and polymethylsilsesquioxane (PMSQ) were used to prepare particles with three distinct layers. Optimized particles were shown to be spherical with an average size ranging from 320 nm (±80 nm) to 220 (±8 nm), which varied with a change in the working distance in the electrohydrodynamic processing. The surface and internal structure and morphology were studied using confocal, transmission and scanning electron microscopy combined with focused ion beam sectioning. Cytotoxicity was shown to be negligible in an in vitro assay. The ability to fabricate such multilayered particles in a single step, under ambient conditions has considerable potential for a range of applications in particular controlled release drug delivery system.